Video made on a Mac : production and postproduction using Apple Final Cut Studio and Adobe Creative Suite - Harrington, Richard, 1972- (Peachpit Press, 2010)
"On a Mac, the sky's the limit for creating professional video. Whether you're an advanced Mac user or just beginning to incorporate Adobe Creative Suite into your Final Cut Studio workflow, you'll learn to apply best-practice techniques to all your video projects. These training videos accompany Video Made on a Mac and can be accessed directly from the lessons that refer to them by clicking the Play buttons you see throughout the pages online or individually from the video tab"--Resource description page.